Self-powered intelligent buoy system by water wave energy for sustainable and autonomous wireless sensing and data transmission. (July 2019) - Xi, Fengben; Pang, Yaokun; Liu, Guoxu; Wang, Shuwei; Li, Wei; Zhang, Chi; Wang, Zhong Lin
Abstract: Harvesting ocean wave energy is a killer application of triboelectric nanogenerator (TENG) for advantages in simple mechanism, high power density and high efficiency at low frequency. Here we report a self-powered intelligent buoy system (SIBS), in which a high-output multilayered TENG is used for water wave energy harvesting. With a power management module, the output voltage can be converted and regulated as a steady DC voltage of 2.5 V for the operations of a microprogrammed control unit (MCU), several micro sensors and a transmitter. With the intelligent monitoring mechanism of the MCU, the harvested energy can be deployed for each sensor with different priority and data transmission cycle, and the SIBS can be at standby and active status by itself at different energy levels. At a wave frequency of 2 Hz, the SIBS can provide an average output power density of 13.2 mW/m 2 and realize sustainable and autonomous wireless sensing for acceleration, magnetic intensity and temperature in range of 15 m, with amount of 19 bytes every 30 s. The SIBS has first demonstrated a complete TENG-based micro-energy solution for self-powered intelligent system, including energy harvesting, management, deployment and utilization, with an unattended manner and infinite lifetime. As a significant milestone for the TENG, this work has provided a universal platform for self-powered wireless sensor network nodes and exhibited broad prospects in internet of things, big data, artificial intelligence and blue energy. Graphical abstract: We propose a self-powered intelligent buoy system (SIBS), including a high-output multilayered TENG for harvesting water wave energy, which can be used for sustainable and autonomous wireless sensing and data transmission. Image 1 Highlights: A self-powered intelligent buoy system (SIBS) is proposed, in which a high-output multilayered TENG is used for water wave energy harvesting. With a power management module, the output voltage can be converted and regulated as a steady DC voltage of 2.5 V for the operations of a microprogrammed control unit (MCU), several micro sensors and a transmitter. With the intelligent monitoring mechanism of the MCU, the harvested energy can be deployed for each sensor with different priority and data transmission cycle, and the SIBS can be at standby and active status by itself at different energy levels. This work has provided a universal platform for TENG-based self-powered wireless sensor network nodes and exhibited broad prospects in internet of things, big data, artificial intelligence and blue energy.